Handbook of Research on Modernization and Accountability in Public Sector - Azevedo, G.; Oliveira, J.; Rui Marques; Augusta Ferreira (2018)
The global financial and economic crisis has promoted the discussion on how ethical, transparent and rigorous accountability on public sector institutions is. Therefore, that have been undertaken within the public sector were triggered by the new vision of the State’s role which has been designated by the New Public Management (NPM). In the context of these reforms, the topic of accountability has becoming increasingly important. Underpinned in NPM assumptions, it is common sense that these reforms shall be undertaken through a progressive introduction of management tools, performance evaluation, and reporting of financial/non-financial indicators suitable to public sector institutions. In this way, it is crucial the dissemination of management tools that will allow public institutions improving their accountability. In the same line, it is also crucial the dissemination of tools that will allow managers promoting information on how management is being conducted and goals achieved. Intertwined with the topic of transparency of the public management this would help improving citizens’ and other regulatory entities’ confidence levels. On the one hand, this publication intends to gather investigations and empirical researches on these tools that unveil how public institutions implement and carry out the reforms designed by the NPM. On the other hand, the evaluation of the status quo of the reforms and the promotion of good practices in the management of public institutions are also relevant. The creation of an independent publication with the goal to spread worldwide the findings of theoretical, empirical and experimental studies can be a fruitful tool to promote modernization and transparency in the public administration. Besides, it would help unveil the relationships between regulators and those regulated by them that could foster strengthening civil society confidence in the information disclosed by public institutions.